Model Pelatihan, Pembinaan dan Pendampingan Usaha Sala Lauak di Ulakan Pariaman Sumatera Barat - Handayani, Desi; Yondri, Surfa (Jurusan Akuntansi Politeknik Negeri Padang, 2015)
This article discusses the model of training, development and accompaniment of small business of sala Lauak in Ulakan. The purposes of this project are to increase and improve: 1) Understanding of partner to business planning and management by transferring knowledge to improve their ability in accounting and simple book keeping. 2) Their ability to do process traditional food hygienically, using supported tools of production (Frying and packing) 3) The value added of traditional food and their income through product diversification, developing new recipes ,and variety of product sold. 4) Their Services in sales by re lay out stall and sales method in order to comfort their buyer; 5) their product quality by supporting partner get legality of production. 6) Finding the right model for training by sharing method and discussion also direct practice, 7) Finding model of development and empower the community to be role model of conceptual, hygienic and competitive development of region